Anti-Diabetic Activity-Guided Studies Of Syzygium Polyanthum (Wight) Leaf Extracts And Elucidation Of Their Mechanisms Of Action - Widyawati, Tri (2015)
Anti-diabetic activity guided studies were performed on the leaves of syzygium polyanthum, a popular traditional medicinal herb in north sumatera, indonesia. The anti-diabetic activity was evaluated by determining whether the extracts lowered the blood glucose levels (bgl) of normal rats (hypoglycaemic test), inhibited the rise of bgl of intraperitoneally glucose- loaded rats (glucose tolerance test) and lowered bgl of streptozotocin-induced diabetic rats. Dried powdered s. Polyanthum leaves were extracted serially with petroleum ether (pee), chloroform (ce), methanol (me) and water (we). In diabetic rats, single-dose administration of the extracts showed that only me reduced bgl. However, upon repeated-dose administration for 6 days both pee and me reduced bgl significantly. Therefore, liquid-liquid partition was used to fractionate me into the following fractions: chloroform (cf), ethyl acetate (eaf), n-butanol (n-bf) and water (wf). Repeated administration of cf and wf decreased bgl of diabetic rats. Cf was shaken with n-hexane to yield an undissolved fraction (sf-1) and a dissolved fraction (sf-2). Onlysf-1 lowered bgl of diabetic rats. Gc-ms identified the presence of squalene (sq)in me, cf and sf-1. Repeated administration of sq reduced bgl of diabetic rats.This suggests that sq is one of the compounds in s. Polyanthum leaf that contributeto its anti-diabetic activity. Repeated-dose for 12 days of me, cf, wf, sf-1 and sqproved that me was the most active blood glucose lowering agent.